Adaptive Artifact Removal From Intracortical Channels for Accurate Decoding of a Force Signal in Freely Moving Rats - Khorasani, Abed; Shalchyan, Vahid; Daliri, Mohammad Reza (Frontiers in Neuroscience, 2019)
Intracortical data recorded with multi-electrode arrays provide rich information about kinematic and kinetic states of movement in the brain-machine interface (BMI) systems. Direct estimation of kinetic information such as the force from cortical data has the same importance as kinematic information to make a functional BMI system. Various types of the information including single unit activity (SUA), multiunit activity (MUA) and local field potential (LFP) can be used as an input information to extract motor commands for control of the external devices in BMI. Here we combine LFP and MUA information to improve decoding accuracy of the force signal from the multi-channel intracortical data of freely moving rats. We suggest a weighted common average referencing (CAR) algorithm in order to valid interpretation of the force decoding from different data types. The proposed spatial filter adaptively identifies contribution of the common noise on the channels employing Kalman filter method. We evaluated the efficacy of the proposed artifact algorithm on both simulation and real data. In the simulation study, the average R2 between the original and reconstructed signal of all channels after applying the proposed artifact removal method was computed for input SNRs in the range of -45 to 0 dB. Weighted CAR method can effectively reconstruct the original signal with average R2 higher than 0.5 for input SNRs higher than -10 dB in case of adding simulated outlier and motion artifacts. We also show that the proposed artifact removal algorithm 33 percent improves the accuracy of force decoding in terms of R2 value compared to standard CAR filters.